PENETAPAN KADAR ANDROGRAFOLID EKSTRAK TERSTANDAR HERBA SAMBILOTO (Andrographis paniculata (Burm.f) Nees) DARI TIGA DAERAH BERBEDA BERDASARKAN PENGARUH KETINGGIAN TEMPAT TUMBUH, INTENSITAS CAHAYA, PH DAN KELEMBABAN TANAH - , HARTANTI MULYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Creat (Andrographis paniculata (Burm.f) Nees) is one of the medicinal plants with a variety of benefits that has long been used by society in traditional medicine. The extract of medicinal plant is needed to be standardized to improve the quality, safety and efficacy products of traditional medicine. The level of the active compounds of medicinal plants can be affected by various environmental factors. This study aims to determine the quality standards parameters value of creat herb extract, to determine the effect of growth place variations to the level of andrographolide in the creat herbs extract from Dlingo, Prambanan and Kalibawang, and to know the areas where produce the creat with the highest level of andrographolide. Creat herb extraction is done by maceration using ethanol 70%. The extract is then standardized and the level of andrographolide is determined by TLC-densitometry method. The level of andrographolide extract were compared based on the effect of growing place altitude, light intensity, pH and soil moisture. The test results were analyzed statistically using SPSS with 95% confidence level. The results showed that the extract standardization meet the requirements except for drying shrinkage and total ash content. There were significant differences in the results of the extracts standardization test of the three regions. Andrographolide concentration of the extract ranges from 27.43 to 28.83 % w/w. The highest level of andrographolide is produced by creat from Prambanan area. The differences in altitude of growth place do not give significant effect on andrographolide level. The difference of light intensity, pH and soil moisture can provide significant effect on level of andrographolide.